2021
DOI: 10.38034/nps.v29i68.606
|View full text |Cite
|
Sign up to set email alerts
|

Grupos reflexivos de gênero para homens no ambiente virtual - primeiras adaptações, desafios metodológicos e potencialidades

Abstract: Este artigo tem por objetivo problematizar a adaptação de metodologias grupais reflexivas sobre gênero ao sistema de encontros online mediados por programas que permitem reuniões no espaço virtual.  Relata-se o desafio de manter uma postura teórico-filosófica e metodológica alinhada a processos reflexivos, coconstrução de espaços relacionais de discussão, respeito à diversidade e problematização das relações de gênero, atentos a um novo contexto social e a produção de novas desigualdades. Busca-se trazer à ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…Some studies indicate the appropriate time for assessments, suggesting 15 months of follow-up to verify the consistency of former participants' non-violent behavior (Veloso;Nativity, 2013). Beiras, Bronz, and Schneider (2020) proposed the insertion of activity monitoring and evaluation as they are carried out. This procedure favors participants by promoting an additional reflection on the relevance of the activity and application in their own lives and that of facilitating teams, who can adopt a posture of constant improvement of their work.…”
Section: Evaluation Of Projects and Main Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies indicate the appropriate time for assessments, suggesting 15 months of follow-up to verify the consistency of former participants' non-violent behavior (Veloso;Nativity, 2013). Beiras, Bronz, and Schneider (2020) proposed the insertion of activity monitoring and evaluation as they are carried out. This procedure favors participants by promoting an additional reflection on the relevance of the activity and application in their own lives and that of facilitating teams, who can adopt a posture of constant improvement of their work.…”
Section: Evaluation Of Projects and Main Resultsmentioning
confidence: 99%
“…In general, we find gaps in the evaluative management of the group activities in Brazil, which could be remedied with continuous evaluation when possible, external guidance, updated documentation, and quality control mechanisms (Veloso;Nativity, 2013). In any case, the literature deems evaluation of group projects as fundamental and, thus considers it as the main difficulty to be overcome (Beiras et al, 2020;Veloso;Natividade, 2013;(Rothman et al, 2003). In Latin America, self-assessment is the most widely used evaluation mechanism, despite its low reliability Rothman et al, 2003), a fact also confirmed in our panorama that, once again, enables the quantitative knowledge of gaps in the literature (Beiras et al, 2020;Toneli;Borders;Ried, 2017;Veloso;Nativity, 2013).…”
Section: Evaluation Of Projects and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beiras orienta projetos de pesquisa e extensão, assim como discentes de mestrado e doutorado nas temáticas de masculinidades, violências, gênero, saúde do homem e segurança pública. Beiras et al, 2021;Beiras & Bronz, 2016, para maiores informações).…”
unclassified